2017
DOI: 10.1002/ajh.24929
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary stomatocytosis: An underdiagnosed condition

Abstract: Hereditary stomatocytoses are a wide class of hemolytic anemias characterized by alterations of ionic flux with increased cation permeability that results in inappropriate shrinkage or swelling of the erythrocytes, and water lost or gained osmotically. The last few years have been crucial for new acquisitions in this field in terms of identifying new causative genes and of studying their pathogenetic mechanisms. This review summarizes the main features of erythrocyte membrane transport diseases, dividing them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 53 publications
(106 citation statements)
references
References 124 publications
(229 reference statements)
2
95
0
8
Order By: Relevance
“…Among the patients originally diagnosed as DHS we identified a 35‐year‐old male, RP1_5, showing a causative PIEZO1 mutation in heterozygous state, thus confirming the clinical suspicion of DHS1 . Interestingly, the patient exhibited also homozygosity for the most common causative mutation of CDAII, the Glu109Lys‐ SEC23B (Table ) .…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…Among the patients originally diagnosed as DHS we identified a 35‐year‐old male, RP1_5, showing a causative PIEZO1 mutation in heterozygous state, thus confirming the clinical suspicion of DHS1 . Interestingly, the patient exhibited also homozygosity for the most common causative mutation of CDAII, the Glu109Lys‐ SEC23B (Table ) .…”
Section: Resultssupporting
confidence: 62%
“…Diagnosis was based on history, clinical findings, laboratory data, morphological analysis of peripheral blood and/or aspirated bone marrow, whenever available . For HS/HST patients, diagnosis was also based on indirect tests (osmotic fragility of erythrocyte, AGLT50, EMA binding test), as well as on ektacytometry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron overload represents the most harmful complication of the chronic anemia, as it can lead to organ damage with subsequent failure of the involved tissues. Indeed, we can observe liver cirrhosis, heart failure, diabetes, and hypergonadotropic hypogonadism with related subfertility in some patients . We recently demonstrated that the pathogenesis of iron overload in CDAII is related to the over‐expression of the erythroblast‐derived hormone ERFE, leading to hepcidin suppression …”
Section: Discussionmentioning
confidence: 99%